Between Reality and Delusion: Psychological Case Study of a Paranoid Schizophrenia Patient in a Rehabilitation Setting - Rifdah Shafa Nafilah; Nanda Audia Vrisaba (International Conference on Psychology and Education (ICPE), 2025)
This article presents a clinical case study of a 42-year-old male patient diagnosed with paranoid schizophrenia who was undergoing rehabilitation at Panti Karya Asih. The study aims to understand the patient’s psychological profile by exploring behavioral patterns, developmental background, and psychosocial stressors. Data were collected using a combination of autoanamnesis, alloanamnesis, structured interviews, observation, and review of medical and psychosocial records over a three-week period. The findings were analyzed using several psychological theories, including Erikson’s psychosocial development theory, Baumrind’s parenting style theory, and Adler’s theory of individual psychology.